Five new species of Centorisoma Becker from China, with an updated key to world species (Diptera, Chloropidae) - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2014)
A review of the species of the genus Centorisoma Becker from China is provided. The following 5 species are described as new to science: C. convexum sp. nov., C. mediconvexum sp. nov., C. neimengguensis sp. nov., C. pentagonium sp. nov. and C. sexangulatum sp. nov. An updated key to the world species of genus Centorisoma is given.